Primary Ovarian Carcinoid Tumor Arising in a Case of Bilateral Mature Teratoma: A Rare Case Report - Dhal, Ipsita; Guha, Priyadarshini (Asian Pacific Journal of Cancer Biology, 2023)
Primary carcinoid of ovary arising in mature solid teratoma is immensely unusual. We report a case of 51-year-old postmenopausal woman came to our emergency room with a complaint of lower abdominal pain, back pain and vomiting. On physical examination a palpable, mobile abdominal mass was noted reaching up to the pelvis. Tumor marker CA-125 was 26.0 U/ml, human chorionic gonadotropin was < 2mIU/ml, serum AFP was <1.3ng/ml, carcinoembryonic antigen level was 1.2mg/ml. Contrast enhanced computed tomographic (CECT) scan of the abdomen revealed a heterogeneously enhancing mass arising in the left adnexa measuring 13x8x15cm showing significant solid component with areas of fat and calcification. No peritoneal disease and abdominal lymphadenopathy. CT findings were suggestive of teratoma. The patient underwent hysterectomy with bilateralsalpingo-oophorectomy. Histopathological examination of left ovary revealed features of carcinoid tumor arising in a mature solid teratoma and right ovary revealed features of mature cystic teratoma.